BRONKOSKOPI SEBAGAI PROSEDUR DIAGNOSTIK DAN TERAPEUTIK PENYAKIT PARU - Sari, Elsa Purnama; Khairsyaf, Oea; Medison, Irvan (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2021)
Abstract Bronchoscopy is a medical procedure that provides tracheobronchial visualization by placing an optical instrument (bronchoscope) into the airways and is performed by a competent doctor. Bronchoscopy was invented by Gustav Killian in 1897 and since then the techniques have continued to develop. In 1966 Shigeto Ikeda introduced flexible bronchoscopy with fiber optic imaging technology. This is a revolution in the field of bronchoscopy. As cases of lung disease become more complex and the need for minimally invasive procedures, the contribution of bronchoscopy becomes increasingly important. This procedure has had significant developments in the last two decades. The latest bronchoscopy technology allows us to look outside the endobronchial tree to the mediastinum using endobronchial ultrasound (EBUS). Then the small nodules located in the periphery can also be traced for sampling using an electromagnetic navigation bronchoscopy (ENB). We can also manipulate the airway muscles to reduce asthma symptoms using bronchial thermoplasty. This paper is written to describe the basic principles of bronchoscopy and its clinical application in the diagnostic and therapeutic measures of pulmonary disease. Keywords: Bronchoscopy, Diagnostic, Therapeutic